Fiscal Decentralization as an Instrument for Economic Development of Local Government in Albania (European Journal of Marketing and Economics, 2018)
A decentralized governance refers to the restructuring or reorganization of authority in order to have a system of co-responsibility between central government institutions, where regional and local level are in accordance with the principle of subsidiarity. This process aims to increase the overall quality and effectiveness of the system governance, enhancing the authority and capacities of the subnational level. One of the most critical approaches to adapt decentralization from theory into practice is its clear understanding of the concept, so be able to better predict what decentralization means, how well it can be planned and implemented, which are its implications and how the challenges can be over-comed. On the other side fiscal decentralization as a core element of financial instruments is related to the creation of opportunities for the financing of supported functions or so-called subsidized. It requires not only transferring financial resources and fiscal authority to local units, but they must be predictable in order to make planning possible enough to fulfill the tasks with transparence and autonomously. The aim of this paper is to briefly study how this process is implemented in Albania, if its principles are applied and how it has affected local government development. As it will be further described and explained, reforms made in this order have emphasized political decentralization, while the focus shifted to administrative , but not considerably into fiscal aspect.
Keywords: Local Government, Fiscal Decentralization, Financial Instrument, Economic Development